The myth of austerity: Empirical evidence from the eurozone countries - Anna Wildowicz-Giegiel (e-Finanse: Financial Internet Quarterly, 2019)
The paper discusses the impact of austerity policy on economic performance in the eurozone countries after the global crisis that occurred in 2007-08. The undertaken fiscal consolidation efforts to cut government expenditure and increase government taxes which begun in 2010, aimed to return sustainability in public finance as the rapid growth in sovereign debt was observed in many economies, especially in the South Europe. The implemented austerity policy under the external pressure not only amplified recession but also caused the further deterioration of public finance characterized by large deficits and increasing public debt. Based on the literature and empirical findings, the issue of austerity policy and its potential consequences on growth is examined. The research aim is to explore both advantages and disadvantages of austerity, focusing on the macroeconomic conditions which accompanied it and the impact of such policy on economic growth in the eurozone countries. The hypothesis of the negative influence of austerity on economic performance is verified on the basis of recent economic literature and conducted empirical research. Both descriptive analysis and dynamic panel regression based on two-step Generalized Method of Moments was used. Data from 2010-17 for the eurozone countries served to prove the existence of a key negative relationship between austerity policy and economic growth in economies that experienced deep great recession
Keywords: H30; H60; H62; H63; H87; 330; austerity; economic growth; cyclically-adjusted primary budget balance